(untitled) (JONAH : Journal of Nursing and Homecare, 2025)
A pregnant woman is a woman who conceives from conception to the birth of the fetus. Physiological changes in pregnant women cause discomfort during pregnancy. The most common complaint felt is low back pain. Low back pain will increase in intensity as you get older in pregnancy. Management that can be done to overcome low back pain is with warm compresses of red ginger. The purpose of this study is to describe the application of warm compresses of red ginger to overcome low back pain in third trimester pregnant women in the Working Area of the Payung Sekaki health center. This research method is a descriptive method with a case study approach conducted in the Working Area of the Payung Sekaki Health Center on April 22-25, 2024. The subjects in this study were two III trimester pregnant women who experienced low back pain. The results showed that the pain scale before the application of red ginger warm compress in subject I was 6 and the pain scale in subject II was 5, which is in the moderate pain category. The scale of pain after applying warm compresses of red ginger in subjects I and II was 1, namely in the category of mild pain. It is expected that respondents can increase knowledge about red ginger warm compresses and can do red ginger warm compresses on III trimester pregnant women independently.